Alpha-synuclein overexpression reduces neural activity within a basal ganglia vocal nucleus in a zebra finch model - Brian R. Dominguez; Gabriel Holguin; Madeleine S. Daly; Reed T. Bjork; Stephen L. Cowen; Julie E. Miller (PLoS ONE, 2026)
Changes in vocal pitch, loudness, and timing are prevalent in Parkinson’s Disease (PD) and a target for early intervention and treatment. The neural mechanisms underlying these impairments are not understood, motivating work in animal models. The adult male zebra finch songbird is uniquely poised for these studies given vocally-dedicated brain nuclei and a quantifiable output (birdsong). Our prior publication revealed that injection of an adeno-associated virus (AAV5) expressing the human (h) alpha-synuclein (h SNCA , a-syn) gene into basal ganglia vocal nucleus Area X results in elevated insoluble a-syn protein and parkinsonian-like changes including softer, shorter, and reduced vocalizations compared to controls. Here, we test the hypothesis that AAV-h SNCA overexpression reduces the firing rate of specific neuronal sub-types in Area X using in vivo recordings in anesthetized finches. Five classes of neurons were differentiated in AAV-treated finches based on waveform width (narrow vs. wide) and firing rates (low vs. high). We found that neurons in the AAV-h SNCA group with wide waveforms exhibited reduced firing rates and enhanced post-peak rebound compared to AAV controls. No differences in firing rate nor waveform shape were detected for the narrow waveform neurons. Our findings provide the first characterization of early a-syn-driven neural activity changes in vocal control neurocircuitry.